Phycoremediation of meat processing wastewater by using microalgae scenedesmus sp. - Ahmad Latiffi, Nur Atikah (2018)
Wastewater produced from Meat Processing Wastewater (MPWW) contains high nutrient loads which can induce eutrophication and cause water quality to deteriorate as it has been claimed that this type of wastewater is difficult to treat due to different types of processed meat and factory activities. The objective of this study was to analyse the ability of phycoremediation technology in order to assess its potential use as in treating MPWW and biomass by-product production. Scenedesmus sp., a type of microalgae, was employed to investigate the effects of a number of factors namely pH, temperature, light intensity, photo period and reduction in nutrients. The factors were measured through the growth rate of biomass productivity and removal efficiency. Subsequently, the design expert method was used to predict the optimal flocculation efficiency of aluminium sulphate for biomass harvesting. It was found that Scenedesmus sp. has a higher biomass productivity in the pH range of 7 to 8, temperatures between 25°C to 40°C, light intensity at 4000 lux and a photoperiod of 12 hours light/12 hours dark. These conditions show a significant influence on biomass productivity at a concentration of 1×106 cells/mL. Furthermore, the highest removal of nutrients was up to 77% for ammonia, orthophosphate, total nitrogen and total phosphorus, followed by chemical oxygen demand at 64%. On the other hand, the optimum flocculation efficiency of 97.54% was found to be best for biomass harvesting. These discoveries are significant as they showed that phycoremediation is suitable and has the potential to be implemented in treating MPWW, specifically in tropical Malaysia.